The Diversity of Macroscopic Fungi in the Nutmeg Plantation (Myristica fragrans Houtt) in Desa Gunung Kerambil, Tapaktuan, Aceh Selatan - Axnesia Ike Rianto; Samingan Samingan; Iswadi Iswadi (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2019)
Macroscopic fungi growth is influenced by environmental factors. Nutmeg plantations generally cannot stand with heat, so the protective plants are needed. Protective plants will reduce the intensity of light and make a microclimate so that the plantations become moist. This study aimed to determine the types and diversity of macroscopic fungi found in nutmeg plantations. Data collection is carried out by exploratory survey methods and subjective sampling. The research location was divided into 3 stations, namely station I on the riverside, station II in the mountain area and station III around the residential area with each station having 10 transects. The measured parameters include the species diversity index. Data were analyzed using the diversity index formula then also carried out a descriptive analysis which included images, descriptions of fungi, and taxonomic hierarchies. The results of this research on the diversity of macroscopic fungi in the nutmeg plantation of Gunung Kerambil, Tapaktuan, South Aceh, found 28 macroscopic fungi classified into 19 genera and 12 families with the dominating genus are Trametes. The macroscopic fungi diversity index in the nutmeg plantation in Gunung Kerambil, Tapaktuan, South Aceh is in the moderate category with a score of 2.96.